Eye Movement Study on Attention Bias to Body Height Stimuli in Height Dissatisfied Males - Chen, Fuguo; Liu, Jie; Chen, Shuanghong; Chen, Hong; Gao, Xiao (Frontiers in Psychology, 2017)
The present study investigated attention bias in response to height-related words among young men in China. 47 [26 high height dissatisfied (HHD) and 21 low height dissatisfied (LHD)] men performed a dot-probe task. Eye movement (EM) recordings showed that compared to LHD men, HHD men had an avoidance bias in response to height-related words, which was revealed by less frequent first fixations on both tall-related and short-related words, and showed significantly shorter first fixations on short-related words. There was no other significant difference in EM indices (i.e., first fixation latency and gaze duration) between two groups. In addition, HHD participants were significantly slower than LHD participants when responding to probes preceded by short-related words, while there was no difference when probes were preceded by tall-related or neutral words. In sum, the present results indicate that HHD men selectively avoid cues related to short height.